Influence of organic matter and texture on the compactability of Technosols - Paradelo, R.; Barral, M.T. (Catena (Giessen), 2013)
The effect produced by adding increasing rates of a municipal solid waste compost on the susceptibility to compaction of three materials of mineral origin was determined. These were quartz sand (85% sand), slate processing fines (78% silt), and commercial bentonite (75% clay), selected due to their highly homogeneous particle size that can provide index information about materials with different textures. The maximum density of compaction of these materials increased in the sequence bentonite<slate processing fines<quartz sand, while the moisture corresponding to the maximum density (critical water content) followed the inverse order. The addition of increasing rates of compost (about 3%, 7% and 14% dry weight) resulted in general in flatter compaction curves and reduced maximum bulk density. The highest rate of compost reduced the maximum density of the quartz sand from 1.88 to 1.33Mgm−3, from 1.54 to 1.22Mgm−3 for the slate processing fines, and from 1.16 to 1.00Mgm−3 for the bentonite. The addition of compost also increased the critical water content, although only at the highest rates. The effect was more important for the sand, whose critical water content increased from 10.4% to 29.1%; for the slate processing fines it increased from 25.2% to 36.2%; and for bentonite it increased from 38.8% to 52.4%. In general, the extent of the effect of compost addition decreased at the same time as the dominant particle size of the material tested. •Compost reduced the compactability of three materials of contrasted texture.•The reduction in compactability was proportional to the rate of compost used.•The effectiveness in reducing compactability was greater the coarser the texture.